Specific prolongation of allograft survival by a T-cell-receptor-derived peptide. - Goss, J A (1993)
Allograft rejection results from the specific recognition by host CD8+ T cells of allogeneic major histocompatibility complex (MHC) molecules on the tissue graft. The specificity of this cellular response is determined by the molecular interaction of the T-cell receptor (TCR) on host T cells with the MHC molecule and its bound ligand on the grafted tissue. To better understand the precise manner by which the TCR interacts with the MHC-peptide complex and how to therapeutically intervene, we have studied the allogeneic response to the mouse class I MHC molecule Ld. In this report, the therapeutic potential of a synthetic peptide derived from the TCR V beta 8 variable region that predominates in responses to Ld was tested. This V beta 8-derived peptide was found to dramatically and specifically block the in vivo and in vitro allogeneic response to Ld. Furthermore, this specific blocking is not dependent upon the presence of V beta 8+ effector cells nor does the V beta 8 peptide bind to the Ld ligand binding cleft. We propose that this peptide functions as an antagonist, competing with the native TCR for recognition of the Ld molecule.